A bis-indole/carbazole based C5-curcuminoid fluorescent probe with large Stokes shift for selective detection of biothiols and application to live cell imaging. Issue 4 (20th December 2019) - Bhattacharjee, Pinaki; Chatterjee, Sourav; Achari, Anushree; Saha, Abhijit; Nandi, Debkumar; Acharya, Chiranjit; Chatterjee, Kasturi; Ghosh, Surajit; Swarnakar, Snehasikta; Jaisankar, Parasuraman
Abstract : A series of heterocyclic C5-Curcuminoid (PJ1–PJ6 ) having large Stokes shift (Δ λ = 104–173 nm) have been synthesized under the microwave irradiation and PJ1 has been utilized for selective detection of thiols in A375 cells and apoptosis in AGS cells. Abstract : A series of heterocyclic C5-curcuminoids (bis(arylmethylidene)acetones) (PJ1–PJ6 ) having a large Stokes shift (Δ λ = 104–173 nm) have been synthesized for the selective detection of cysteine (Cys), homocysteine (Hcy) and glutathione (GSH) in living cells. The compounds were synthesized using a new methodology via deacetylation under microwave conditions. The photophysical properties of these compounds have been studied. Prominent colour changes from bright yellow to colourless in the presence of thiols were observed for PJ1 . Live cell imaging has been employed with PJ1 for the utilization of the probe to detect homocysteine in A375 cells and apoptosis in AGS cells.